Bringing the commercial determinants of health out of the shadows: a review of how the commercial determinants are represented in conceptual frameworks. (18th January 2020) - Maani, Nason; Collin, Jeff; Friel, Sharon; Gilmore, Anna B; McCambridge, Jim; Robertson, Lindsay; Petticrew, Mark P
Abstract: Background: The term 'commercial determinants of health' (CDOH) is increasingly focussing attention upon the role of tobacco, alcohol and food and beverage companies and others—as important drivers of non-communicable diseases (NCDs). However, the CDOH do not seem to be clearly represented in the most common social determinants of health (SDOH) frameworks. We review a wide range of existing frameworks of the determinants of health to determine whether and how commercial determinants are incorporated into current SDOH thinking. Methods: We searched for papers and non-academic reports published in English since 2000 describing influences on population health outcomes. We included documents with a formal conceptual framework or diagram, showing the integration of the different determinants. Results: Forty-eight framework documents were identified. Only one explicitly included the CDOH in a conceptual diagram. Ten papers discussed the commercial determinants in some form in the text only and fourteen described negative impacts of commercial determinants in the text. Twelve discussed positive roles for the private sector in producing harmful commodities. Overall, descriptions of commercial determinants are frequently understated, not made explicit, or simply missing. The role of commercial actors as vectors of NCDs is largely absent or invisible in many of the most influential conceptual diagrams. Conclusions: Our current public health models may risk framing public health problems and solutions in ways that obscure the role that the private sector, in particular large transnational companies, play in shaping the broader environment and individual behaviours, and thus population health outcomes.